Analiza kartografskega opismenjevanja v slovenskih in angleških osnovnih šolah - Hojnik, Tina; Hus, Vlasta (Revija za elementarno izobraževanje, 2012)
Analysis of cartographic literacy development in Slovenian and English primary schools. The purpose of cartographic literacy development is training individuals for proper use of maps. Maps are present in many aspects of our lives, therefore, their proper reading and interpretation is very important for the development of one's space perception and consequently also for self-study, and general knowledge. Cartographic literacy of primary school pupils from most European countries is at a relatively low level. Therefore, we carried out a study were we tried to established how cartographic literacy development appears and upgrades within Slovenian and foreign curricula. The article presents the results of a comparison of selected criteria in Slovenian and English curricula for primary level. Comparative results confirmed that cartographic literacy development received a maximum attention in the revised Slovenian social studies curriculum, but with one deficiency, namely, cartography is introduced (too) late. Some aspects of cartographic literacy development in the English geography curriculum indeed occur sooner than in the Slovenian curriculum, but because of the general definition of attainment targets and lack of recommendations for cartographic education in the English curriculum, the cartographic literacy development depends primarily on teachers and their cartographic knowledge. A combination of an open curriculum and the teacher's poor cartographic knowledge pushes cartographic literacy development in the background, which is why paying attention to this subject in the curricula or textbooks is of paramount importance.
Keywords: education; curriculum; cartographic literacy developšment; teaching methods; teaching techniques